Digitalization of Identification and Initial Assessment in Inclusive Education at Elementary Schools: A Systematic Literature Review - Fauziah Wulansari; Minsih Minsih; Choiriyah Widyasari (FKIP - Universitas Riau, 2026)
This systematic literature review examines the digitalization of identification and initial assessment processes for children with special needs (ABK) in inclusive elementary education over the past five years. Guided by PRISMA standards, relevant studies were collected from databases such as Google Scholar, ERIC, and DOAJ. The review identifies three primary categories of digital applications: digital screening and diagnostic tools, e-assessment and reporting platforms, and assistive technologies with accessibility features. Findings indicate that digitalization improves administrative efficiency, ensures more consistent documentation, supports data-driven monitoring, and strengthens collaboration between teachers and parents. Despite these advantages, significant challenges remain, including inconsistent validity and reliability of assessment instruments, unequal access to technology, limited teacher digital competencies, and ethical concerns related to data privacy and algorithmic bias. The review emphasizes that effective implementation depends not only on technological tools but also on ecosystem readiness, teacher professional development, ethical governance, and child-centered design. Furthermore, major gaps persist in long-term empirical research, standardized assessment workflows, and governance systems to address privacy protection and bias reduction. Overall, digitalization offers substantial potential to enhance inclusive education assessment practices when supported by comprehensive planning and responsible implementation.